2007
DOI: 10.1158/0008-5472.can-06-3665
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 1 and Glutamate Signaling in Human Melanoma

Abstract: Recently, several laboratories have started to investigate the involvement of glutamate signaling in cancer. In previous studies, we reported on a transgenic mouse model that develops melanoma spontaneously. Subsequent studies in these mice identified that the aberrant expression of metabotropic glutamate receptor 1 (GRM1) in melanocytes played a critical role in the onset of melanoma. Confirmation of the etiologic role of GRM1 in melanoma development was shown in a second transgenic line with GRM1 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
343
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 176 publications
(375 citation statements)
references
References 27 publications
30
343
0
2
Order By: Relevance
“…This is confirmed by observed elevation of glutamine, alanine, citrate, asparagine, and decreased hypoxanthine in the tumor bearing mice which are intermediates of the pyrimidine metabolism, the pyruvate metabolism, the TCA cycle, the glutamate metabolism, and the purine metabolism, respectively. Glutamate signaling in cancer has stimulated extensive research interest recently and has shown great importance in human melanoma development [37][38][39][40]. Increased glutamate concentration has also been reported by previous studies as a common phenomenon in tumors [41].…”
Section: Discussionmentioning
confidence: 73%
“…This is confirmed by observed elevation of glutamine, alanine, citrate, asparagine, and decreased hypoxanthine in the tumor bearing mice which are intermediates of the pyrimidine metabolism, the pyruvate metabolism, the TCA cycle, the glutamate metabolism, and the purine metabolism, respectively. Glutamate signaling in cancer has stimulated extensive research interest recently and has shown great importance in human melanoma development [37][38][39][40]. Increased glutamate concentration has also been reported by previous studies as a common phenomenon in tumors [41].…”
Section: Discussionmentioning
confidence: 73%
“…Riluzole functions by inhibiting glutamate release from neurons and noncompetitively blocking its uptake by post-synaptic neurons, therefore preventing neuronal glutamate toxicity [14]. Our group showed that Riluzole could disrupt glutamatergic signaling in tumor cells by disrupting glutamate release to the extracellular environment of mGluR1 expressing melanoma cells, limiting the availability of the ligand to maintain receptor activation [15]. One consequence of reduced extracellular glutamate is a decrease in cell growth, as has been shown for many transformed cells including melanoma [16].…”
Section: Introductionmentioning
confidence: 83%
“…It has been observed that ectopic expression of metabotropic glutamate receptor 1 (GRM1) in melanocytes is sufficient to induce spontaneous melanoma development in vivo and transformation in vitro [37,38]. Moreover; the ectopic expression of GRM1 mediated melanoma agenesis is independent of the genotype of either BRAF or NRAS [39]. Until now the mechanism by which the aberrant expression of glutamate receptor 1 in melanocytes leads to oncogenesis remains unknown.…”
Section: Molecular Pathwaysmentioning
confidence: 99%